2007
DOI: 10.3340/jkns.2007.41.4.272
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Traumatic Hemorrhage of the Basal Ganglia

Abstract: Bilateral traumatic hemorrhage of the basal ganglia is an extremely rare neuropathologic entity. This report describes a 50year-old man with bilateral basal ganglia hemorrhage with occipital fracture of the skull after head trauma. The mechanism of development of traumatic hemorrhage of the basal ganglia has been not clear. But, it is presumed to be secondary to rupture of the lenticulostriate or anterior choroidal artery by shearing as a result of acceleration/deceleration forces. We briefly summarize our unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 9 publications
(24 reference statements)
0
48
0
Order By: Relevance
“…Traumatic basal ganglia hemorrhage needs to be differentiated from jpmer spontaneous basal ganglionic hematomas. As in present case, in a previously healthy individual without any history of hypertension 10 with a clear cut history of trauma, and no evidence to suggest any other cause of basal ganglionic hemorrhage.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Traumatic basal ganglia hemorrhage needs to be differentiated from jpmer spontaneous basal ganglionic hematomas. As in present case, in a previously healthy individual without any history of hypertension 10 with a clear cut history of trauma, and no evidence to suggest any other cause of basal ganglionic hemorrhage.…”
Section: Discussionmentioning
confidence: 61%
“…18 The management of the TBGH depends on the neurological status, size of the hematoma, presence of mass effect, and the options include conservative management, open surgery, CT-guided stereotactic, or ultrasound-guided aspiration. [2][3][4]10 In present case, in view of the smaller size of the lesion, we managed the patient conservatively. Traumatic basal ganglia hemorrhage needs to be differentiated from jpmer spontaneous basal ganglionic hematomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mosberg and Lindenberg, 4 in an autopsy of fatal head injury patient, demonstrated massive hematoma in the improvement in all patients managed conservatively. Kimura et al, 13 Katz et al, 3 and Jang et al 7 have also reported favorable outcomes for TBGH with conservative management. Surgical evacuation entails approach to the hematoma via the thalamoganglionic region, leading to further damage of the eloquent areas resulting in possible poor outcome.…”
Section: Discussionmentioning
confidence: 93%